ANALISIS CEMARAN Escherichia coli DAN Salmonella typhi PADA JAMU GENDONG DENGAN METODE MOST PROBABLE NUMBER (MPN) - Salsabila, Salma Fi; Rahmasari, Khusna Santika; Nur, Achmad Vandian; Pambudi, Dwi Bagus (Fakultas Farmasi Universitas Jenderal Achmad Yani, Indonesia, 2024)
The consumption of jamu kunyit asam and beras kencur is an integral part of Indonesian culture. Jamu kunyit asam, a mixture of turmeric and tamarind, is believed to enhance the immune system and aid digestion. Jamu beras kencur, made from rice and aromatic ginger, is known for boosting stamina and alleviating fatigue. However, the traditional production of jamu, often lacking strict hygiene standards, can lead to contamination by pathogenic microorganisms such as Escherichia coli and Salmonella typhi. This study aims to detect the presence of E. coli and S. typhi in jamu kunyit asam and beras kencur, and to analyze whether these traditional herbal drinks sold across districts in Pekalongan City comply with the established quality standards for traditional medicine. The analysis of pathogenic microorganisms using the Most Probable Number (MPN) method revealed that MPN values in the presumptive test using Lactose Broth and the confirmatory test using Brilliant Green Lactose Broth ranged from 0 to 18.98 MPN/mL. Out of four samples of jamu kunyit asam, one did not meet the permissible contamination limits, and three out of four samples of jamu beras kencur were non-compliant. The complementary tests showed that seven samples were positive for E. coli (samples coded A1, A2, B1, B2, C2, D1, and D2) and four samples were positive for S. typhi (samples coded A1, D1, C2, and D2).